The effect of a phytogenic-based feed additive on concurrent Lawsonia intracellularis and Brachyspira hyodysenteriae infections in pigs - CF Wu; HC Kuo; M Glišić; M Vasiljević; J Raj; J Bošnjak- Neumuller; V Drašković (South African Journal of Animal Science)
This study investigated the efficacy of a commercial phytogenic-based premixed feed additive (PFA) in treating combined Lawsonia intracellularis and Brachyspira hyodysenteriae infections in finishing pigs, with tiamulin/lincomycin treatment as the control. Pigs aged 20 weeks were allocated to PFA treatment (11 pens, 45 pigs per pen) and control (7 pens, 43 pigs per pen) groups for a seven-week experimental period. Floor faecal samples and rectal swabs were collected weekly, and the percentage of pigs per pen with diarrhoea was recorded weekly. The bacterial contents of the samples were determined using real-time polymerase chain reaction, and at the end of the experiment, histological changes in ileal samples were examined. There was an intermittent decrease in L. intracellularis in the control group (from 4.85 to 0.82 DNA log10 copies/μl) and a continuous reduction in L. intracellularis in the PFA group (from 5.69 to 0.64 DNA log10 copies/μl) over a six-week period. B. hyodysenteriae was not detected in rectal swabs from the control group at week six, and an intermittent decrease in B. hyodysenteriae, from 3.04 to 0.26 DNA log10 copies/μl, was observed in the PFA group. Bacterial DNA in the floor faecal samples declined during the seven-week experimental period, as found for the rectal swabs. There were no cases of diarrhoea from week two onwards in the control group and week three onwards in the PFA group. The results of this study indicate that a PFA rich in essential oils has a therapeutic effect comparable to that of tiamulin/lincomycin in pigs with proliferative enteropathy and swine dysentery.